Delineation of the movement disorders associated with FOXG1 mutations. (10th May 2016) - Papandreou, Apostolos; Schneider, Ruth B.; Augustine, Erika F.; Ng, Joanne; Mankad, Kshitij; Meyer, Esther; McTague, Amy; Ngoh, Adeline; Hemingway, Cheryl; Robinson, Robert; Varadkar, Sophia M.; Kinali, Maria; et al.
Abstract : Objective: The primary objective of this research was to characterize the movement disorders associated with FOXG1 mutations. Methods: We identified patients with FOXG1 mutations who were referred to either a tertiary movement disorder clinic or tertiary epilepsy service and retrospectively reviewed medical records, clinical investigations, neuroimaging, and available video footage. We administered a telephone-based questionnaire regarding the functional impact of the movement disorders and perceived efficacy of treatment to the caregivers of one cohort of participants. Results: We identified 28 patients with FOXG1 mutations, of whom 6 had previously unreported mutations. A wide variety of movement disorders were identified, with dystonia, choreoathetosis, and orolingual/facial dyskinesias most commonly present. Ninety-three percent of patients had a mixed movement disorder phenotype. In contrast to the phenotype classically described with FOXG1 mutations, 4 patients with missense mutations had a milder phenotype, with independent ambulation, spoken language, and normocephaly. Hyperkinetic involuntary movements were a major clinical feature in these patients. Of the symptomatic treatments targeted to control abnormal involuntary movements, most did not emerge as clearly beneficial, although 4 patients had a caregiver-reported response to levodopa. Conclusions: Abnormal involuntary movements are a major feature of FOXG1 mutations. Our study delineates the spectrum of movement disorders and confirms an expanding clinical phenotype. Symptomatic treatment may be considered for severe or disabling cases, although further research regarding potential treatment strategies is necessary.